2014
DOI: 10.1093/ofid/ofu058
|View full text |Cite
|
Sign up to set email alerts
|

The Linkage Outcomes of a Large-scale, Rapid Transfer of HIV-infected Patients From Hospital-based to Community-based Clinics in South Africa

Abstract: The rapid transfer of nearly 4000 HIV-infected patients from a hospital-based clinic to community-based clinics had an estimated success of 82%. Close collaboration between transferring and receiving clinics is necessary to ensure that the health gains from PEPFAR funding are maintained.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
33
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 25 publications
3
33
0
Order By: Relevance
“…Two studies evaluating transfer outcomes following clinic-initiated ‘official’ transfer have concluded that nearly all patients actively referred for transfer reach their destination clinic, however timing of transfer linkage was not assessed. (Cloete et al, 2014; O’Connor, Osih, & Jaffer, 2011) Only one prior study has reported on the timeliness of linkage to the new clinic following transfer, concluding that nearly all patients making official transfers out of a large hospital-based clinic in Malawi reached their destination facilities, with a mediation duration between departure and re-engagement of 1.3 months. (Yu et al, 2008) All three of these studies, however, have focused on official transfers from a central site to lower level health facilities.…”
Section: Discussionmentioning
confidence: 99%
“…Two studies evaluating transfer outcomes following clinic-initiated ‘official’ transfer have concluded that nearly all patients actively referred for transfer reach their destination clinic, however timing of transfer linkage was not assessed. (Cloete et al, 2014; O’Connor, Osih, & Jaffer, 2011) Only one prior study has reported on the timeliness of linkage to the new clinic following transfer, concluding that nearly all patients making official transfers out of a large hospital-based clinic in Malawi reached their destination facilities, with a mediation duration between departure and re-engagement of 1.3 months. (Yu et al, 2008) All three of these studies, however, have focused on official transfers from a central site to lower level health facilities.…”
Section: Discussionmentioning
confidence: 99%
“…37-39 The Sinikithemba cervical screening policy was based on international guidelines. Specifically, the hospital policy was to offer a Papanicolau test (Pap) within the first 3 months of initiating ART, a second smear within the first year, and annual smears thereafter.…”
Section: Methodsmentioning
confidence: 99%
“…Sinikithemba was required to transfer all patients between March and the end of June 2012, during which patients visiting the clinic underwent a group counseling session explaining the clinic closure and transfer procedures (Cloete et al, 2014). Patients were transferred to primary healthcare clinics, community health centers, or were referred to hospital-based clinics based on their ART regimen or co-morbid conditions.…”
Section: Methodsmentioning
confidence: 99%
“…Our prior quantitative study estimated that nearly 20% of patients may not have linked to care and may have experienced a treatment interruption (Cloete et al, 2014). The qualitative study presented here was performed to assess potential reasons for these findings, including patient perceptions of the transfer process and factors impacting continued care engagement.…”
Section: Introductionmentioning
confidence: 99%